Psychometric assessment of the PROMIS Fatigue Short Form 6a in women with moderate-to-severe endometriosis-associated pain - Robin Pokrzywinski; Ahmed M. Soliman; Eric Surrey; Michael C. Snabes; Karin S. Coyne (SpringerOpen, 2020)
Abstract Background Endometriosis is a common problem in women of reproductive age and has impacts on health-related quality of life and productivity. Fatigue is an important part of the burden of endometriosis, it is not often included as an endpoint in clinical trials. Objectives The study assessed the psychometric properties of the PROMIS Fatigue Short Form 6a in women with moderate-to-severe endometriosis-associated pain. Methods In a phase III double-blind, placebo-controlled clinical trial (NCT01620528), women aged 18-49 years with moderate-to-severe endometriosis-related pain were randomized to elagolix 150 mg once daily, elagolix 200 mg twice daily, or placebo for 6 months. PROMIS Fatigue and dysmenorrhea and non-menstrual pelvic pain (NMPP) scores were assessed at baseline and months 1, 3, and 6, and Patient Global Impression of Change (PGIC) was assessed at months 1, 3, and 6. Reliability (internal consistency and test-retest reliability), construct validity (convergent and known groups validity), and responsiveness were evaluated. Results The analysis included 871 women, mean age 31.5 years. Internal consistency supported a single concept (Cronbach's alpha 0.93). For the 238 patients with no change in PGIC at month 1, the intraclass correlation coefficient for the PROMIS Fatigue T-score was 0.7 and paired t-test statistically significant (2.84, p = 0.0049). Correlations with other measures were expected to be fairly low as concepts were not redundant. The PROMIS Fatigue discriminated among known groups with mean scores of 55.3, 62.3, and 65.8 at month 3 (PGIC improvement, no change, worsening, respectively). Statically significant discrimination, and change score responsiveness, were seen using clinically relevant anchors (dysmenorrhea and NMPP) at months 3 and 6 between responders and non-responders. Anchor-based (PGIC) responsiveness showed significant improvement from baseline to months 3 and 6 (p < 0.0001). Conclusions PROMIS Fatigue has good reliability, validity, and responsiveness in women with moderate-to-severe endometriosis-associated pain.